Thermal and Mechanical Properties of a Biobased Unsaturated Polyester Resin - Jia, Jinrong; Huang, Zhixiong; Wang, Yanbing (Asian Journal of Chemistry, 2013)
A biobased soybean oil monoglyceride unsaturated polyester resin (SOMGUPR) was prepared by two steps using soybean oil, glycerol, 1.2-propanediol, maleic anhydride and phthalic anhydride. FT-IR, 1H NMR, DSC and DMA were employed to study the chemical structure and thermal properties of this unsaturated polyester resin. The results showed that SOMGUPR containing 30 % soybean oil monoglyceride (SOMG) exihibited optimial combination properties, where glass transition temperature (Tg), tensile strength and impact strength were 71 ºC, 7.6 Mpa and 85 KJ/m2, respectively. The side reaction between SOMG and maleic anhydride had not occured as evidenced by 1H NMR spectroscopy. The reactivity of SOMGUPR containing 30 wt % SOMG was lower than that of SOMGUPR without it. The more cotent of SOMG up to 40 wt %, the lower tensile strength. The impact strength increased with the increasing amount of SOMG content up to 30 wt % and then stabilized at nearly 100 KJ/m2.